2019
DOI: 10.1007/s00408-019-00201-y
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Lung Protective Angiotensin Converting Enzyme-2 by Meconium in Human Alveolar Epithelial Cells: A Potential Pathogenic Mechanism in Meconium Aspiration Syndrome

Abstract: Background Pancreatic digestive enzymes present in meconium might be responsible for meconium-induced lung injury. The local Renin Angiotensin System plays an important role in lung injury and inflammation. Particularly, angiotensin converting enzyme-2 (ACE-2) has been identified as a protective lung enzyme against the insult. ACE-2 converts pro-apoptotic Angiotensin II to anti-apoptotic Angiotensin 1-7. However, the effect of meconium on ACE-2 has never been studied before. Objective To study the effect of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Cultures were maintained at 37°C and 5% CO 2 in humidified incubator. Cells were cultured until maximal confluence was reached in order to get high levels of ACE2 in cells [ 31 ]. In order to study the interaction of RAS modulators or anti-inflammatory compounds with SARS-CoV-2 Spike RBD-Fc protein, cells were pretreated or not pretreated with the AT1 receptor blocker Candesartan (1 μM; 4791, Tocris) or the ACE inhibitor Captopril (50 ng/ml; C4042, Sigma) for 24 h. Then, 1 µg/ml of SARS-CoV-2 Spike RBD-Fc protein (40592-V02H, Sino Biological) was added to the cells for 3 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Cultures were maintained at 37°C and 5% CO 2 in humidified incubator. Cells were cultured until maximal confluence was reached in order to get high levels of ACE2 in cells [ 31 ]. In order to study the interaction of RAS modulators or anti-inflammatory compounds with SARS-CoV-2 Spike RBD-Fc protein, cells were pretreated or not pretreated with the AT1 receptor blocker Candesartan (1 μM; 4791, Tocris) or the ACE inhibitor Captopril (50 ng/ml; C4042, Sigma) for 24 h. Then, 1 µg/ml of SARS-CoV-2 Spike RBD-Fc protein (40592-V02H, Sino Biological) was added to the cells for 3 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Yang et al showed that SARS-CoV exhibits augmented replication in mice that overexpressed the human ACE2 enzyme under the mouse ACE2 promoter [ 61 ]. However, multiple studies have shown a potentially protective role of ACE2 activity in lung injury and lung failure [ 62 , 63 ]. These studies suggest potential adverse effects of both ACE2 overexpression and ACE2 inhibition in SARS-CoV-2 infection.…”
Section: Hypertension Inflammation and Covid-19mentioning
confidence: 99%
“…Expression pattern of ACE and ACE2 in human disorders (↑: up-regulation, ↓: down-regulation). Hypertensive human kidney/heart Ang II regulates ACE/ACE2 mediated by the AT1-ERK/p38 pathway in mRNA and protein levels -↓ ACE2 knockout ALI-induced mice Loss of ACE2 expression resulted in severe ALI phenotypes and rhuACE2 can protect mice from severe acute lung injury [16] Neonatal lung injury -↓ Alveolar epithelial A549 cells Proteolytic enzymes in meconium effectively degraded ACE-2 in human A549 cells and decreases its protective activity [37] Smoking -↑ Human lung tissue Smokers may be more susceptible to 2019-nCov [38] Inflammatory bowel disease (IBD) -↑ CD, UC patients with IBD ACE2 activity and Ang [1][2][3][4][5][6][7] concentrations and the ACE/ACE2 ratio were higher in patients with IBD [39] S. Ghafouri-Fard, et al Vascular Pharmacology 130 (2020) 106680 Table 2 The effect of different treatments on the expression pattern of ACE and ACE2 (↑: up-regulation, Table 3 Association between ACE/ ACE2 polymorphisms and human disorders in different populations.…”
Section: Tablementioning
confidence: 99%